2023
DOI: 10.3389/fmicb.2023.1086021
|View full text |Cite
|
Sign up to set email alerts
|

Integration of text mining and biological network analysis: Identification of essential genes in sulfate-reducing bacteria

Abstract: The growth and survival of an organism in a particular environment is highly depends on the certain indispensable genes, termed as essential genes. Sulfate-reducing bacteria (SRB) are obligate anaerobes which thrives on sulfate reduction for its energy requirements. The present study used Oleidesulfovibrio alaskensis G20 (OA G20) as a model SRB to categorize the essential genes based on their key metabolic pathways. Herein, we reported a feedback loop framework for gene of interest discovery, from bio-problem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 118 publications
0
7
0
Order By: Relevance
“…tRNA-Sec regulates the synthesis of selenocysteine, which plays crucial role in the oxygen resilience (reducing reactive oxygen species) of OA G20. In our other study, using a text-mining and proteinprotein network approach, we found a gene SelA (synthesizes Sec from Ser-tRNA) in the OA G20 genome to be essential [42]. Researchers have identified a selenocysteine-containing enzyme (formate dehydrogenase H) in E. coli [93].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…tRNA-Sec regulates the synthesis of selenocysteine, which plays crucial role in the oxygen resilience (reducing reactive oxygen species) of OA G20. In our other study, using a text-mining and proteinprotein network approach, we found a gene SelA (synthesizes Sec from Ser-tRNA) in the OA G20 genome to be essential [42]. Researchers have identified a selenocysteine-containing enzyme (formate dehydrogenase H) in E. coli [93].…”
Section: Discussionmentioning
confidence: 92%
“…OA G20 is a well-studied model SRB for MIC due to biofilm formation [21,42,43]. The OA G20 genome has 3257 CDSs and 66 tRNA genes (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…The outcome exceeded expectations: some projects earned slots for presentation at the international IEEE Bioinformatics conference in 2022 [5][6][7][8], yielding three Machine Learning models published in a journal [9][10][11][12][13][14][15][16][17][18]. Feedback from participants a rmed the success of this experience, underlining the potential for integrating convergence research into the curriculum through problem-based learning.…”
Section: Pre-post Ratings Work Ow Understandingmentioning
confidence: 99%
“…For example, by employing manual curation and a predictive model, Saxena et al have successfully identified key essential gene sets of Oleidesulfovibrio alaskensis G20 using the sulfate‐reducing bacterium model and classified these genes through pan‐genome analysis. The results indicated that most essential genes belonged to the core gene category, whereas essential genes in other categories may be environment‐specific [ 195 ]. Furthermore, Wu et al proposed a strategy to reduce the genome size of B. subtilis while simultaneously ensuring the retention of core and essential genes [ 196 ].…”
Section: Introductionmentioning
confidence: 99%